Silicato de Cálcio como atenuante do estresse salino em mudas de maracujazeiro amarelo - Souza, Tarso Moreno Alves de (2018)
The study about the initial growth response of plants submitted to the condition of artificial stresses is an important alternative to understand the survival and adaptation capacity of the cultures under stressful conditions, being able to contribute to the development of management strategies. The objective of this study was to evaluate the effects of silica fertilization and irrigation with saline water on the initial development parameters of yellow passion fruit seedlings. The experiment was carried out at Fazenda Favela, Km 334, BA 052, in an area destined to the production of seedlings, located in the municipality of João Dourado-BA, a city belonging to the micro-region of Irecê-BA. The experimental design was a randomized block design, with four replications, considering five experimental plants as experimental unit. The treatments were arranged in a 4 x 3 factorial scheme, referring to four concentrations (0, 2.22, 4.44 and 6.66 g plant-1) of calcium silicate and three levels of salinity of irrigation water - ECw (0.5, 1.7 and 4.0 dS m-1). The seedlings of the cultivar “BRS Gigante Amarelo” were grown in polyethylene bags with a capacity of 0.5 dm3. The substrate used in the experiment was composed of soil, washed sand and tanned bovine manure in a 1: 1: 1 ratio. After the stabilization of the emergency, at 30 days after sowing (DAS), thinning was done, maintaining only one plant per container, and began the application of saline treatments and doses of calcium silicate, the latter being applied in three plots at 30, 45 and 60 days after sowing. At 90 days after sowing, when 70% of the seedlings presented the first tendril, the plants were collected and analyzed with respect to height, stem diameter, leaf number, leaf area, shoot weight, root and total dry mass. The use of well saline water of 1.7 dS m-1 was not restricted to the production of yellow passion fruit cv. “BRS Gigante Amarelo”. The use of water with salinity of 4.0 dS m-1 restricted the growth and accumulation of biomass of passion fruit seedlings, with root dry matter being the most affected variable. The application of calcium silicate doses increases the growth and biomass accumulation of yellow passion fruit seedlings independent of water salinity. Plants irrigated with low salinity water respond linearly to increased calcium silicate doses. The application of calcium silicate in the average dose of 3.5 g per plant mitigates the saline stress on the growth and accumulation of biomass of passion fruit seedlings irrigations with salinity up to 4.0 dS m-1